The arithmetic relations between total expenditure and the resulting current and financial account balances as determinants of the revenue-related need for means of payment in an economy - Wolfgang Stützel (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
Introductory note by the translators: In the following paragraphs, Stützel derives some balance mechanic relationships between revenue and expenditure surpluses, on the one hand, and the volume of credit necessary to finance these, on the other. He then moves on to consider the balance sheet of the banking sector and its relationships with the volume of credit. Insights from both exercises are subsequently used to synthesise the 'orthodox' and 'modern' theories of credit. The few parts of Stützel (1958 [1978]: 208–219) which were excluded from the translation are the ones in which Stützel directly refers to other parts of the book which are not translated here, as well as some footnotes referring to issues or publications which were topical at the time at which Stützel was writing but which are of very limited interest for our purposes. Furthermore, we omit a short passage in which Stützel briefly introduces the 'straddle effect', a concept which is important in his discussion of the quantity theory of money (ibid.: 229–255) but which does not feature any further in the section we are translating. For more on the quantity equation from a balance mechanics perspective, see Tarne (2016). The text below is a direct translation from Stützel without any changes or amendments, including Stützel's use of emphases and quotation marks.
Keywords: 330